(untitled) (Al-Academy, 2023)
Intellectual and material displacement is one of the design strategies through many mechanisms and means, and depends on the idea of changing the shape within the internal spaces at times and has concepts related to the transformation at other times. And represented by the boxes for travelers, the research problem emerged through the following question: (What is the effectiveness of displacement in the formal structures in the interior design of historical sites), and the aim of the study is to reveal the reality of the use of historical internal spaces and to determine the formal displacement that occurs as a result of change and transformation, and it included two topics, the first topic Transformation and the effectiveness of formal displacement in the interior spaces and the second topic: the transformation in the interior design of public buildings. And other moral ones are linked to the historical space and the partial or comprehensive effects that occur on them that affected them differently through the preservation or the dismantling of the design system. in a different format.